Empirical Explorations of Guitar Players’ Attitudes Towards Their Equipment and the Role of Distortion in Rock Music - Herbst, Jan-Peter (Current Musicology, 2020)
This article has its source in a larger research project on distorted guitar playing in rock music which focuses on distortion’s effect on playability and expressiveness, its psychological influences on chord perception, composition, and production, and on issues regarding genre aesthetics. While most work on rock music and guitar cultures has either studied recorded and transcribed music or the star’s personality, behavior, and medial staging, this empirical study mainly focuses on amateur and semi-professional musicians, but it also evaluates statements of professional guitarists of various prominence. It explores guitar players’ views and attitudes as well as their preferred equipment, based on the theoretically grounded assumption that musicians’ use of equipment is strongly connected with genre conventions.